SEROLOGICAL STATUS OF EPSTEIN-BARR VIRUS IN BONE MARROW DONOR AND RECIPIENT AND ITS IMPACT ON POST-TRANSPLANT OUTCOMES: EBV serostatus and impacts on pos transplant - CHAVES, Ana Vitória; AMORIM MOTA SEGUNDO, HERCULES; Viana Campos, Sarah Emanuelle; Barroso Duarte, Fernando; Sampaio Nunes Barroso, Karine (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
The Epstein-Barr virus (EBV) is a highly immunogenic herpesvirus that infects more than 90% of healthy individuals and can remain latent in B lymphocytes for years. In this context, in immunocompromised patients, such as those undergoing bone marrow transplantation (BMT), viral reactivation can occur in up to 63% of cases. Among the main risk factors for viral reactivation are donor-recipient incompatibility, EBV IgG-positive donors, and conditioning regimens using lymphodepleting drugs such as anti-thymocyte immunoglobulin, high-dose cyclophosphamide, and corticosteroids. Therefore, weekly EBV monitoring is recommended during the first 100 days post-transplant to detect viremia early and enable preemptive intervention, either by reducing immunosuppression or using anti-CD20 monoclonal antibodies. These strategies aim to reduce viremia progression and the incidence of post-transplant lymphoproliferative disease (PTLD). This study seeks to estimate the serological profile of bone marrow donors and recipients and its relationship with the incidence of post-BMT viral reactivation. Additionally, it aims to evaluate monitoring and preemptive treatment strategies for managing high-risk patients at the Walter Cantídio University Hospital from 2020 to 2024, while also defining the incidence of PTLD secondary to BMT. Keywords: Bone Marrow Transplantation, Epstein Barr Virus, EBV, lymphoma